L-glutamine and L-glutamate in diets with different lactose levels for piglets weaned at 21 days of age - Molino,Juliano Pelição (2012)
This study was developed to evaluate the effects of adding L-glutamine and L-glutamate in diets with no lactose or with 4.0 or 8.0% lactose inclusion for piglets weaned at 21 days old. One hundred and eight piglets with initial weight of 6.12±0.70 kg were allotted in a complete randomized block design, in a 3 × 2 factorial arrangement, with six treatments, six replicates, and three piglets per experimental unit. The experimental diets were supplied from 21 to 35 days. From 36 to 49 days, animals received the same diet with no lactose inclusion, but the animals in the treatments with L-glutamine + L-glutamate in the previous phase continued to receive diets containing these ingredients. There was no interaction between the level of lactose and the inclusion of L-glutamine + L-glutamate on the parameters evaluated. The levels of lactose did not affect the performance of piglets in either of the two periods. Adding L-glutamine and L-glutamate in the diet positively influenced the weight gain of pigs from 21 to 49 days of age and increased the villous height in the duodenum, jejunum and ileum. Inclusion of L-glutamine + L-glutamate in diets for piglets weaned at 21 days of age improves the performance and the intestinal mucosa morphology, regardless of lactose addition.